Guidance for the treatment of adult growth hormone deficiency with somapacitan, a long-acting growth hormone preparation - Bidlingmaier, Martin; Biller, Beverly M.K.; Clemmons, David; Jørgensen, Jens Otto L.; Nishioka, Hiroshi; Takahashi, Yutaka (Frontiers in Endocrinology, 2022)
Adult growth hormone deficiency (AGHD) is a rare endocrine disorder characterized by an abnormal body composition, metabolic abnormalities associated with increased cardiovascular diseases, bone loss, and impaired quality of life. Daily subcutaneous injections with recombinant growth hormone (GH) can alleviate the abnormalities associated with AGHD. Several long-acting GH (LAGH) preparations are currently in development that aim to reduce treatment burden for patients receiving daily GH injections. Somapacitan (Sogroya®; Novo Nordisk, Denmark) is the first LAGH preparation that has been approved for treatment of AGHD in the United States, Europe, and Japan. The recent approval of somapacitan and anticipated approval of other LAGH molecules presents new questions for physicians planning to treat AGHD with LAGH in the future. Differences in the technologies used to prolong the half-life of recombinant GH are expected to result in variations in pharmacokinetic and pharmacodynamic profiles between preparations. Therefore, it is essential that physicians understand and consider such variations when treating patients with these novel GH replacement therapies. Here, we present a set of treatment recommendations that have been created to guide physicians initiating therapy with somapacitan in patients with AGHD who are eligible for GH replacement. Furthermore, we will review the published data that underlie these recommendations to explain the rationale for the treatment and monitoring advice provided.